Peace Congress in Sistova (1790–1791) in the reports of the Warsaw press (Władza i polityka w czasach nowożytnych. Dyplomacja i sprawy wewnętrzne, 2020)
In the article, the Author outlined the course of the Austrian-Turkish peace negotiations in Sistova based on information published in the Polish-language Warsaw press. The talks, started in December 1790, were helding with the participation of representatives of the Triple Alliance of Loo (1788): Prussia, Great Britain and the Netherlands. As a result, Austria made peace with the Ottoman Empire (4 VIII 1791) on the basis of the territorial “status quo”, which terminated lasting since 1788 war between both countries. A separate convention stipulated that the emperor would retain Old Orşova with the adjacent district and a small area of Croatia till the Una river, with the Cettin and Drežnik fortresses. All in all, supplementing the press reports with findings of the literature on the subject, the Author managed to obtain a relatively complete and not yet fully studied in Polish historical literature image of the issue indicated in the title.